2020
DOI: 10.1101/2020.07.24.219246
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Maintenance of mitochondrial integrity in midbrain dopaminergic neurons governed by a conserved developmental transcription factor

Abstract: The degeneration of dopaminergic (DA) neurons in the substantia nigra is a hallmark of Parkinson’s Disease (PD). Dysregulation of developmental transcription factors is implicated in dopaminergic neurodegeneration, but the underlying molecular mechanisms remain largely unknown. Drosophila Fer2 is a prime example of a developmental transcription factor required for the birth and maintenance of midbrain DA neurons. Using an approach combining ChIP-seq, RNA-seq, and genetic epistasis experiments with PD-linked ge… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 99 publications
(168 reference statements)
0
5
0
Order By: Relevance
“…We previously demonstrated that flies exposed to hydrogen peroxide (H 2 O 2 ) or paraquat for 24 h display selective loss of DA neurons in the PAM cluster (Fig. 1A) 12,13,20 . To evaluate dopaminergic neurodegeneration from a circadian perspective, we developed a short-term H 2 O 2 treatment protocol that can be performed at six timepoints across the day.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…We previously demonstrated that flies exposed to hydrogen peroxide (H 2 O 2 ) or paraquat for 24 h display selective loss of DA neurons in the PAM cluster (Fig. 1A) 12,13,20 . To evaluate dopaminergic neurodegeneration from a circadian perspective, we developed a short-term H 2 O 2 treatment protocol that can be performed at six timepoints across the day.…”
Section: Resultsmentioning
confidence: 97%
“…The adult fly midbrain contains approximately eight clusters of DA neurons projecting to various brain regions 9 . Functional impairments or loss of DA neurons in the protocerebral anterior medial (PAM) and protocerebral anterior lateral 1 (PPL1) clusters have been consistently observed in PD models, in addition to the losses in other clusters [10][11][12][13] . The PAM cluster comprises ~130 neurons per hemisphere, accounting for approximately 80% of fly brain DA neurons.…”
Section: Introductionmentioning
confidence: 99%
“…CircRNA is often abnormally expressed and expressed in cerebrovascular disease and high tissue speci city (Meng et al, 2022). Therefore, targeted therapy targeting circRNA may be developed into a new way to treat cerebrovascular disease in the future, and theoretically, it may not cause the harmful side effects to healthy tissues (Miozzo et al, 2022). In the traditional clinical diagnosis and treatment, imaging diagnosis, such as CT, MRI and other technologies as well as the application of disease markers, for the diagnosis and treatment of AIS patients provide a certain guiding role (Nichols et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Many clinical trials have reported that effective blood ow reperfusion can reduce acute ischemic brain injury and improve the clinical prognosis of patients with AIS (Hellwig et al, 2022;Rog-Zielinska et al, 2015). At present, in addition to intravenous thrombolytic therapy as the rst-line treatment, intraarterial thrombolytic therapy can be used for patients with a time window of 4.5 h or less than 6 h (Miozzo et al, 2022;Yao and Vanduffel, 2022). In a study published in the New England Journal of Medicine in 2018, Nogueira et al suggested that mechanical thrombectomy could be used in patients with AIS onset longer than 6 h and less than 24 h (Choi et al, 2020;Rog-Zielinska et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation